Implementation of the Surtax on Non-Metallic Mineral and Rock Taxes in Bandar Lampung City: An Analysis of Siyāsah Tanfīdhiyyah on Mayor Regulation Number 1 of 2025 - Irsyad, Barry; Frenki; Kartika S (Al-Risalah, 2026)
This study aims to analyze the implementation of Bandar Lampung Mayor Regulation Number 1 of 2025 concerning Procedures for the Collection of Non-Metallic Mineral and Rock Tax (MBLB) and the MBLB Tax Surtax through the perspective of Siyāsah Tanfīdhiyyah. The analysis results indicate that the substantive provisions contained in Articles 7 and 8 of the Mayor Regulation are in line with the principle of Amānah (accountability) through an integrated payment system, as well as the principle of al-‘Adālah (justice) through the obligation to maintain honest business records in order to prevent excessive taxation. The enforcement of administrative sanctions within this regulation is categorized as a form of Ta‘zīr, aimed at preserving the authority of the law and public welfare (maṣlaḥah mursalah). This study further emphasizes that the normative effectiveness of this policy depends on the integrity and transparency of production data to prevent practices of al-bāṭil (unlawful acquisition of wealth). In conclusion, the MBLB tax surtax policy in Bandar Lampung City is not merely a fiscal instrument, but also a manifestation of the executive authority’s obligation to maintain a balance between natural resource exploitation and environmental restoration for the welfare of society.